Examining Ethiopia's live animal and meat value chain - Asrat Ayza Wakaso; Yesihak Yusuf Mummed; Yonatan Kassu Yesuf (Heliyon)
This review examines the efficiency of live animal and meat value chain from producers to consumers in Ethiopia. Ethiopia has a large livestock population, but the marketing system for live animals and meat remains underdeveloped. Several challenges hinder efficient transactions, including poor infrastructure, illegal cross-border trade, lack of market information, traditional production methods, and absence of grading systems. As a result, producers often receive low prices and have limited access to export markets. The key actors in the value chain, are input suppliers, farmers, traders, cooperatives, exporters, abattoirs, and consumers. However weak linkages and lack of coordination among these actors lead to inefficiencies. The trends in Ethiopia's livestock exports have fluctuated, with live animal exports exceeding meat product exports due to supply constraints and inability to meet quality standards for processed meat. The review highlights opportunities to strengthen the value chain through infrastructure upgrades, improved market information systems, promoting quality standards, and aligning production with export requirements. Coordinated efforts involving the government, private sector, and development partners are needed to address the challenges and unlock the potential of Ethiopia's meat animal value chain for the benefit of producers, traders, consumers, and the overall economy.